Konsep Wajah Yang Lain dalam Filsafat Emmanuel Levinas sebagai Dorongan Moral melalui Konten Media Katolikpedia.id - Stefanus Poto Elu (Jurnal Filsafat dan Teologi Katolik, 2025)
The concept of the face of the other in Emmanuel Levinas’s philosophy remains a relevant and enduring philosophical idea. The presence of the face interrupts the existence of the “I” and simultaneously calls it to ethical action. This moral summons constitutes an inherent ethical responsibility for every individual. In today’s digital era, the internet has formed a virtual space in which the face of the other emerges in new forms, including through digital content. This study examines how the concept of the face of the other is manifested in the content published by Katolikpedia.id across various digital platforms such as its website, Instagram, YouTube, and TikTok. The aim of this research is to explore the extent to which these contents awaken ethical awareness and encourage moral action among followers, readers, and the general public. This study employs a qualitative method, using a combination of literature review and content observation. The findings reveal that the content of Katolikpedia.id, both explicitly and implicitly, communicates an ethical call to society to adopt a moral stance and act responsibly. Thus, digital media becomes a new space for the presence of the face of the other and for ethical encounters in contemporary contexts.